2009
DOI: 10.1007/s00467-008-0966-z
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephritis associated with acquired cytomegalovirus infection in a 19-month-old baby

Abstract: Membranous nephritis (MN) is a rare form of glomerulonephritis in childhood, with an incidence of 0.8 to 6.7% based on renal biopsy specimens. Although the disease is considered to be idiopathic in the majority of cases, especially in adults, MN has been associated with various infectious agents, such as hepatitis Beta virus. The natural history of MN in childhood remains unknown because of its rarity, and to the best of our knowledge, no case of MN linked to cytomegalovirus (CMV) infection in an immunocompete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
5
1
3
Order By: Relevance
“…Some scholars also reported iMN accounted for 31.8% of membranous nephropathy, mean age was 43.9 ± 13.2 years old, and were mainly distributed between 40 to 60 years old, male and female ratio 1.53:1; [ 17 ] but some other data showed that in developed countries, iMN accounted for 60% to 80%, the sex ratio of MN patients was 1.3 to 2.3:1. [ 18 , 19 ] These results are different from our center that indicate that different country or different geographic environment in some country may have a certain impact on the development of disease.…”
Section: Discussioncontrasting
confidence: 87%
“…Some scholars also reported iMN accounted for 31.8% of membranous nephropathy, mean age was 43.9 ± 13.2 years old, and were mainly distributed between 40 to 60 years old, male and female ratio 1.53:1; [ 17 ] but some other data showed that in developed countries, iMN accounted for 60% to 80%, the sex ratio of MN patients was 1.3 to 2.3:1. [ 18 , 19 ] These results are different from our center that indicate that different country or different geographic environment in some country may have a certain impact on the development of disease.…”
Section: Discussioncontrasting
confidence: 87%
“…Since two of the non‐CTLA4‐Ig‐treated baboons died with high copies of bCMV in lungs, and development of bCMV may influence the development of proteinuria , we tested the sera for evidence of bCMV infection in the early postoperative period in recipients of Study 2. Despite all animals developing proteinuria in the first 20 days in the non‐CTLA4 Ig‐treated group in Study 2, no bCMV replication was observed in three of four baboons by POD 20 and the remaining baboon had only 19.4 copies/ml of serum at POD 10 and 242.95 copies/ml of serum at POD 20 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CMV has been implicated in nephritis and rejection in renal transplant recipients [De Keyzer et al, 2011]. Additionally, it has been suggested that CMV may be involved in childhood nephritis [Platt et al, 1985;Matsukura et al, 2006;Georgaki-Angelaki et al, 2009] and congenital nephrotic syndrome [Evans and Lyon, 1991;Batisky et al, 1993;Giani et al, 1996;Eddleston et al, 1997;Barbi et al, 1998;Frishberg et al, 2003;Besbas et al, 2006]. Since children with renal disease are treated generally by immunosuppressive drugs, these patients are considered to be at high risk for reactivation of herpesviruses.…”
Section: Introductionmentioning
confidence: 99%